2012
DOI: 10.1097/mao.0b013e3182536dc2
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Multi-Channel Cochlear Implantation Results in Significant Improvement in Quality of Life

Abstract: Cochlear implant surgery significantly improves health-related quality of life as categorically stratified by the SF-36 questionnaire. These improvements were most evident in the mental health, emotional and social functioning, and physical functioning at work questions of the survey. Cochlear implant recipients younger than 65 years perceive a greater improvement in their level of energy, mental health, and social function compared with those older than 65 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
11

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 32 publications
2
52
0
11
Order By: Relevance
“…Ten studies reported on generic health utility metrics, which included the Short Form-36 (SF-36) [Chung et al, 2012;Damen et al, 2007;Mo et al, 2005], Ontario Health Utilities Index (HUI) Marks II and III [Damen et al, 2007;Faber and Grøntved, 2000;Klop et al, 2007Klop et al, , 2008Sparreboom et al, 2012], the EQ5D, the VAS from the EQ5D, the time trade-off technique (TTO), the Australian Quality of Life (AQoL) instrument [Hawthorne et al, 2004], the Hopkins Symptom Check List 25 (HSCL-25) [Mo et al, 2005], the Psychological General Well-Being (PGWB) Index [Rembar et al, 2009], and the Glasgow Benefit Inventory (GBI) [Lassaletta et al, 2006]. Although none of these measures are specific to hearing or the effects of CI, some do incorporate hearing ability as part of the measure, as discussed below.…”
Section: Generic Instruments In Adultsmentioning
confidence: 99%
“…Ten studies reported on generic health utility metrics, which included the Short Form-36 (SF-36) [Chung et al, 2012;Damen et al, 2007;Mo et al, 2005], Ontario Health Utilities Index (HUI) Marks II and III [Damen et al, 2007;Faber and Grøntved, 2000;Klop et al, 2007Klop et al, , 2008Sparreboom et al, 2012], the EQ5D, the VAS from the EQ5D, the time trade-off technique (TTO), the Australian Quality of Life (AQoL) instrument [Hawthorne et al, 2004], the Hopkins Symptom Check List 25 (HSCL-25) [Mo et al, 2005], the Psychological General Well-Being (PGWB) Index [Rembar et al, 2009], and the Glasgow Benefit Inventory (GBI) [Lassaletta et al, 2006]. Although none of these measures are specific to hearing or the effects of CI, some do incorporate hearing ability as part of the measure, as discussed below.…”
Section: Generic Instruments In Adultsmentioning
confidence: 99%
“…The benefits of CI regarding auditory speech perception and the implanted person communication have been widely presented (3,4) . Thus, the focus of research in cochlear implants was naturally directed to other areas of research such as evaluating the impact of this device in people's lives, considering the self-esteem, daily activities and social functions, which account for the quality of life (5) . The contribution of studies of this nature is reflected along the CI in interdisciplinary teams, in order to present the results of this intervention on the quality of life of this device users measured methodologically.…”
Section: Introductionmentioning
confidence: 99%
“…The WHOQOL-BREF is one of the most appropriate instruments to assess quality of life as it considers the subjectivity and the multidimensionality in people's lives (14) . Research shows that the cochlear implant (CI) has been an effective clinical resource to improve these individuals quality of life (QOL) (5,6) , in a study that assess a long-term QOL of 32 cochlear implant users with the instrument SF-36 before surgery, a year and 10 years after the CI (15) . These authors found statistically significant difference from preoperative to a year of use in three domains of the instrument (Vitality, Social Functioning, and Mental Health), from a year to 10 years in two domains (Physical aspects and Vitality) and from preoperative to 10 years of use in one domain (Pain).…”
Section: Introductionmentioning
confidence: 99%
“…Satisfaction surveys through questionnaires have been performed for evaluating these positive effects [50][51][52][53] .…”
Section: Discussionmentioning
confidence: 99%